MORTARS FOR THE RESTORATION OF ARCHITECTURAL MONUMENTS OF BUKHARA IX-XVI CENTURIES - Vakhitov, M.; Tulaganov, A.; Tozhiev, I. (International Journal of Psychosocial Rehabilitation, 2020)
In this article, mortars used in the construction of unique architectural monuments of Bukhara were studied. As a result of the studies, modified solutions were obtained for the restoration and restoration of architectural monuments of Bukhara.